Civil Service Reform Strengthening World Bank and IMF Collaboration. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
Civil service reform is often essential to bring about governanceimprovements that are needed for sustainable poverty reduction.A workshop hosted by the World Bank and the IMF in September 2001provided a forum to review the effectiveness of Bank-Fund advice and programs on civil service reform, and to propose ways to improve jointefforts in coming years. Programs in 11 countries were examined, (Benin,Bolivia, Cambodia, Macedonia, Mali, Mongolia, Pakistan, Russia, Tanzania,Yemen, Zambia), and macrofiscal and structural outcomes of Bank-Fund workin those countries considered. This book is a joint publication betweenthe IMF and the World Bank.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet